Accessibility Considerations for Hybrid Courses. (March 2017) - Behling, Kirsten
Abstract : This chapter explores the central questions and issues that faculty and administrators need to consider when designing and implementing hybrid courses to ensure that all students, including those with disabilities, have equal access. The author offers resources on faculty development programs, accessibility checklists, and online resources on universal design that can be applied at a range of campuses. Institutional guidelines around choosing accessible platforms and online learning tools are shared.